2022
DOI: 10.1152/ajpendo.00333.2021
|View full text |Cite
|
Sign up to set email alerts
|

Muscle miR-16 deletion results in impaired insulin sensitivity and contractile function in a sex-dependent manner

Abstract: microRNAs (miRs) are linked to various human diseases including Type 2 Diabetes Mellitus (T2DM) and emerging evidence suggests miRs may serve as potential therapeutic targets. Lower miR-16 content is consistent across different models of T2DM; however, the role of miR-16 in muscle metabolic health is still elusive. Therefore, the purpose of this study was to investigate how deletion of miR-16 in mice affects skeletal muscle metabolic health and contractile function in both sexes. This study was conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Circulating miR-16 was increased in GDM samples ( Figure 5 A) and was reported, together with miR-29a and miR-134, to form a predictive biomarker algorithm for GDM [ 21 ]. Interestingly, deletion of miR-16-5p in skeletal muscle positively correlates with insulin sensitivity [ 79 ], and circulating levels of miR-16-5p are also correlated positively with insulin sensitivity [ 80 ], which is not well-reconciled with circulating miR-16-5p being increased in GDM, which is a state characterized by impaired insulin sensitivity. However, Cao et al (2017) [ 30 ] found circulating miR-16-5p levels to be highly correlated with insulin resistance, measured with the HOMA-IR index.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating miR-16 was increased in GDM samples ( Figure 5 A) and was reported, together with miR-29a and miR-134, to form a predictive biomarker algorithm for GDM [ 21 ]. Interestingly, deletion of miR-16-5p in skeletal muscle positively correlates with insulin sensitivity [ 79 ], and circulating levels of miR-16-5p are also correlated positively with insulin sensitivity [ 80 ], which is not well-reconciled with circulating miR-16-5p being increased in GDM, which is a state characterized by impaired insulin sensitivity. However, Cao et al (2017) [ 30 ] found circulating miR-16-5p levels to be highly correlated with insulin resistance, measured with the HOMA-IR index.…”
Section: Discussionmentioning
confidence: 99%
“…Western blots were carried out as previously described (Lim et al., 2022). Briefly, 20 mg of frozen quadriceps and heart muscle samples were powdered and homogenized in Laemmli buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Functional research on miR-16 has mainly focused on diseases [ 33 , 34 , 35 , 36 ]. Muscle miR-16 deletion results in impaired insulin sensitivity and contractile function in a sex-dependent manner [ 37 ]. miR-16-5p suppression protects human cardiomyocytes against endoplasmic reticulum and oxidative stress-induced injury [ 38 ].…”
Section: Discussionmentioning
confidence: 99%